Current strategies for the management of anomalous origin of coronary arteries from the pulmonary artery - Beyaz, Metin Onur; Çoban, Şenay; Ulukan, Mustafa Özer; Do?an, Mehmet Sait; Erol, Cengiz; Sarıtaş, Türkay; Erdem, Abdullah; Akdeniz, Celal; U?urlucan, Murat; Akçevin, Atıf; Türko?lu, Halil (NLM (Medline), 2021)
INTRODUCTION: The coronary arteries, which have to originate from the aorta, may sometimes rise from the pulmonary artery. This study evaluated clinical and diagnostic findings, treatment methods, and follow up of cases with anomalous coronary arteries arising from the pulmonary artery. PATIENTS AND METHODS: Eight patients with the diagnosis of anomalous left coronary artery from the pulmonary artery (ALCAPA) (N = 6) and anomalous right coronary artery from the pulmonary artery (ARCAPA) (N = 2), between January 2014 and January 2020 from a single center university hospital, were included in the study. Data from patients' demographic characteristics, electrocardiography, echocardiography, angiographic findings, operation, hospitalization, and follow up were evaluated. RESULTS: The study included eight patients (six females and two males) - six patients with ALCAPA and two with ARCAPA. The ages of the patients ranged between 3-135 (average: 53.25) months. The median body weight was calculated as 17.4 kg. Severe mitral valve insufficiency was detected in two patients and two other patients had a moderate degree of mitral insufficiency on echocardiography. Ejection fractions ranged between 16-74%. One patient had perimembranous malalignment large ventricular septal defect with pulmonary stenosis. Operative techniques were Takeuchi procedure (three patients), direct implantation (four patients), and left internal thoracic artery to left main coronary artery bypass (one patient). Mechanical cardiac support was not required in the postoperative period. Mortality did not occur. Mitral insufficiency and ejection fractions improved following correction of the coronary anatomy. CONCLUSION: It is important to diagnose the ALCAPA or ARCAPA, where the coronary artery originates from the pulmonary artery. Patients should be treated before congestive heart failure and fatal complications occur. Surgical correction should be planned regardless of symptom status, even though some of patients reach adulthood with an increased number of collaterals.
Keywords: Coronary Arteries; Pulmonary Artery; Management of Anomalous Origin